Speech sound perception in monolinguals, bilinguals and learners - Language background affects identification and discrimination differently - Tamminen Henna; Peltola Maija S (Australia, 2022)
The categorical nature of speech perception may result in learning difficulties when L2 speech sounds overlap with L1 sound areas. In addition to possible learning difficulties, it may create interesting overlapping phoneme category areas between the bilinguals’ two native languages. Here, we tested how language learners, simultaneous bilinguals and monolinguals perceive the same rounded closed /y/- /ʉ/-/u/ vowel area. In learners and bilinguals this area is divided either into two or three categories in their two languages (Finnish and Swedish, respectively), whereas only the three category division is in use in the monolinguals (Swedish). It seems that second language learners’ learning process is still ongoing since their /ʉ/–/u/ boundary was less sharp in vowel identification than the other two groups’. On the other hand, both learners and bilinguals seem to benefit from being language oriented and from using two languages in their daily lives as they were more sensitive discriminators than the monolinguals.
Proceedings of the 19th International Congress of Phonetic Sciences, Melbourne, Australia 2019